2013
DOI: 10.1080/1359432x.2013.849246
|View full text |Cite
|
Sign up to set email alerts
|

Training, exhaustion, and commitment of temporary agency workers: A test of employability perceptions

Abstract: The aim of this study was to analyse whether the social exchange between temporary agency workers (TAWs) and the client organization is associated with a perception of training. In this study, we developed and tested a moderated mediation model that accounts for TAWs' exhaustion and desire to obtain a direct contract with the client company in the relationship between the perception of training and affective commitment. Our hypotheses were tested on a sample of 425 blue-collar workers from four Portuguese comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 80 publications
2
56
1
Order By: Relevance
“…Previous research has suggested that reciprocation by temporary workers is limited to target-specific training (internal to the client) which increased commitment only to that target (Chambel et al, 2013). Indeed, general (external) training did not increase commitment to the target offering the training.…”
Section: (Anc)mentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research has suggested that reciprocation by temporary workers is limited to target-specific training (internal to the client) which increased commitment only to that target (Chambel et al, 2013). Indeed, general (external) training did not increase commitment to the target offering the training.…”
Section: (Anc)mentioning
confidence: 98%
“…Indeed, while some studies have found that temporary workers report lower levels of commitment (e.g., Biggs & Swailes, 2006; Coyle-Shapiro, Morrow, & Kessler, 2006), other studies have found that temporary workers can display similar or even higher levels of commitment than permanent workers (e.g., De Cuper & De Witte, 2008;Chambel, Sobral, Espada, & Curral, 2013;Haden, Caruth, & Oyler, 2011).…”
Section: (Anc)mentioning
confidence: 99%
“…Such pattern of results is in line with the fact that this modality of employment is involuntary (CIETT, 2012;Lopes and Chambel, 2014) and most TAW worldwide, including Portugal, would rather have a permanent employment contract, and aspire to be hired by the company in which they perform their job. This desire suggests that TAW are highly vulnerable (De Jong and Schalk, 2010), as they avoid showing bad results since they depend on the client organization to fulfill their desires (Chambel, Sobral, Espada and Curral, 2013). Thus, TAW might show dedication towards their work, regardless of their perception of the organization's obligations.…”
Section: Page 15 Of 31mentioning
confidence: 99%
“…Watkins and Marsick 2014). The present study examines TAWs' affective organizational commitment (further referred to as 'affective commitment', or AC), which refers to 'the emotional attachment to, identification with, and involvement in an organization' (Meyer et al 2002, 21) and is generally viewed as an important predictor of employees' performance (Chambel et al 2015;Meyer et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…full-time, indefinite period of time) as a means to maintain staff flexibility and at the same time maintain a competitive position (Chambel et al 2015;Connelly and Gallagher 2004). One of these 'nonstandard' or 'atypical' employment contracts includes temporary agency work: an employment construction in which employees are officially employed via an employment agency and work for a client organization for a limited period of time (Liden et al 2003).…”
Section: Introductionmentioning
confidence: 99%